UNVEILING COMPETITIVE ADVANTAGE AND VULNERABILITIES: A STUDY OF COMMERCIAL BANKS IN KENYA - Wright, S. (Journal of Healthcare Management and Administration (JHMA), 2023)
In today's increasingly uncertain and competitive business environment, organizations face the imperative to monitor and understand their surroundings with greater accuracy in order to ensure survival and success. As environmental challenges and risks continue to escalate, companies must develop advanced competencies to effectively monitor the competitive landscape and maintain their competitive edge. Competitive intelligence has emerged as a critical tool for organizations, not only for protecting against perceived threats and changes, but also for identifying new opportunities and trends. Consequently, understanding and leveraging competitive intelligence has become an essential aspect of strategic planning and management processes. This study examines the relationship between competitive intelligence and organizational performance, aiming to contribute to the limited research on the generalization of this relationship. By utilizing information systems and harnessing the abundance of available information, organizations can generate competitive advantage and foster continuous innovation, leading to long-term survival and prosperity. Competitive intelligence provides numerous benefits, including an objective view of the marketplace, reduced decision-making time, risk minimization, early identification of opportunities and competitor moves, counter-move considerations, input for idea generation, and verification of assumptions and intuition. Moreover, it promotes a proactive decision-making attitude, supports decision prioritization, and encourages a pursuit of excellence. The challenge faced by today's organizations lies in effectively navigating this evolving competitive landscape. Performance measurement plays a crucial role in quantifying the effectiveness and efficiency of actions. While competitive advantage and firm performance have been extensively studied, there is a dearth of research on the relationship between competitive intelligence and performance. This study fills this gap by exploring the value-adding, continuous, and systematic process of competitive intelligence as a means to monitor both internal and external environments. The findings of this research contribute to enhancing organizational decision-making processes and improving overall performance by leveraging the power of competitive intelligence.